Nutrition planning and hydration control during a six-stage Pirineos FIT Endurance trail-running race. A case report - Drehmer Rieger, Eraci; Navarro, Mª Ángeles; Carrera, Sandra; Herrera, Roberto; Sanchis, Carlos; Moreno, Mari Luz (Progress in Nutrition, 2020)
Ultra-endurance competitions are highly demanding sport events for athletes and require a carefully controlled nutrition, hydration and supplementation before, during and after the physical effort. Scientific research has shown a positive relationship between dietetic (caloric and macronutrient ingestion) recommendations and sport performance. This study describes the nutritional and hydration planning applied to an athlete competing at the Pirineos FIT (a semi-self-sufficient trail-running multi-stage event). Diary caloric ingestion was around 4000 Kcal, 550 Kcal were consumed during the race. In general, the athlete maintained the minimal recommendable levels of hydration (2.5% Body Weight Loss) and Borg’s Scale of Exertion (RPE) was used to report subjective perception of fatigue after each stage. Hematological and biochemical parameters showed a normal response to endurance physical exercise. Therefore, the nutrition and hydration planning were successfully applied.